ETIOLOGY OF STROKES AND HEMIPLEGIA IN CHILDREN PRESENTING AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Siddiqui, Tahir Saeed; Rehman, Anis ur; Ahmed, Basharat (Journal of Ayub Medical College Abbottabad, 2006)
Background: Strokes in pediatric age group are not common. However diagnosing the cause of stroke will help in providing preventive and curative treatment. Present study was conducted to find etiology of strokes/hemiplegia in children. Methods: This study was conducted in Department of Pediatrics, Ayub Teaching Hospital Abbottabad from December 2002 to December 2005.All children from two months to fifteen years of age were included in the study. Children with weakness due to acute poliomyelitis and Guillan barre syndrome were excluded. Investigations were based on findings on history and clinical examination and included full blood count, PT, APTT, Platelets count, ECG, Echocardiography, hematocrit, lumber puncture with CSF analysis and culture and CT-scan skull. Data of all the patients presenting with strokes/hemiplegia was entered on prepared proforma. Results: The main etiology of strokes was intracranial infection causing strokes in 23(56.09%)children and majority of children (78.26%) in this group were below five years. Etiology was un-known in 7(17.07%) children after necessary available investigations. Conclusions: Intracranial infection Infections that is meningitis and encephalitis are commonest etiology of strokes and hemiplegia in paediatrics patients presenting at Ayub Teaching Hospital, Abbottabad. Key words: Cerebrovascular Accident, Children, Hemiplegia, Intracranial infections